ANALISIS BOBOT KOMPONEN-KOMPONEN GEDUNG TERHADAP KEANDALAN BANGUNAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - , NUR VIDIATUN CHASANAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Infrastructure facilities in the world is growing with the passing of the level of need and the greater movement of people. One of the infrastructure has been the impact of the level of human movement is building. Building changes physically and financially over time so there should be maintenance and building maintenance. This study has the objective to identify and analyze the weight of each component of the building to the reliability. Identification and analysis of the weight of each component of the building is intended to set priorities for maintaining the condition of the building and its maintenance on the building elements. This study was conducted by distributing questionnaires to the respondents related. The results of this study are weight or percentage of each building component to reliability. The components were processed using Analytical Hierarchy Process (AHP) to produce a percentage, specifically Structure 90%, 10% Non structures, structures below 78%, over 15% structure, roof structure 7%, room 50%, 50% Coverings, Foundation 50%, 50% Sloof, Column 75%, 25% Ringbalk, The horses are 75%, 25% roofs, Nok 69%, 23% Rafters, Battens 8%, 8% ceiling, 46% walls, Doors 20%, 17% window, Floor 8%, 45% window frames, shutters 32 %, 23% window hinge, door frame was 66%, 19% leaf doors, door hinges are 16%, 75% tile and ridge 25%.